Deinstitutionalization and ethnic and religious freelancing: strategies and speeches of the Armenian leaders in Argentina - Levita, Gabriel (2010)
The speeches of several Armenian institutional leaders in Buenos Aires, Argentina are analyzed to identify the processes of quantitative and qualitative transformations. These changes come along with modifications in the practices and representations of Armenian believers. The processes of individualization and deinstitutionalization of religious figures and tendencies to ethnic and religious freelancing are studied in some detail.